ANALISIS IMPLEMENTASI KEBIJAKAN PROGRAM SANTUN LANJUT USIA DI PUSKESMAS BANGETAYU KOTA SEMARANG TAHUN 2014 - Familia Endah Triyani; Anneke Suparwati; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
One of the output indicators mannered elderly health centers program is health care for the elderly and pre-elderly in health centers. Semarang city already has 21 elderly health centers until 2014 mannered One such program is a pilot health centers health centers Bangetayu, but for the scope of services to the elderly and pre-elderly in 2013 is still below the target of DKK. Implementation of a program can be influenced by communication, resources, disposition and bureaucratic structures. This research was conducted in the area of Semarang Bangetayu. This type of research is exploratory research study with a qualitative approach. Data were collected by in-depth interviews using interview guides and observation using the observation checklist sheet for support facilities. Informants research that managers and program leaders mannered elderly health centers and Head of the Section of Maternal and Elderly DKK Semarang, implementing programs in Bangetayu mannered elderly, program coordinator, Head Bangetayu health centers, as well as cross-sectoral officers Bangetayu. The results showed that the delivery of information from DKK to the clinic Bangetayu already done when socializing in 2009 and in 2011 when training both through media exposure. But for clarity of information about health centers mannered elderly only understood in detail by the program coordinator mannered elderly only, this is because refreshing officer only once a year. Resource availability is limited so that the workload is still very high officials. Budget funds are available each year, although still relatively small. Facilities and infrastructure are available already quite complete. Attitude executor also demonstrate commitment and willingness to carrying out the program because it considers part of the task. SOP and the existing guide books. But coordination between DKK to health centers and cross-sectoral Bangetayu still lacking. It is recommended to Semarang City Health Office convey information not only with the clarity of the program coordinator at the health center, but to the rest of the program managers, program managers to the addition of personnel, service programs do not focus on curative services, but the service of preventive, promotive and rehabilitative as well as well as increased coordination to DKK, clinic staff and program delivery across sectors that can be delivered to all officers.